Planting a Seed of Experience – Long Term Effects of a Co-curricular Ecogarden-Based Program in Higher Education in Hong Kong - Cheang, Chi-Chiu; Ng, Wai-Ki; Wong, Yuen-Sam Diana; Li, Wai-Chin; Tsoi, Kwok-Ho (Frontiers in Psychology, 2021)
This paper reports on the long-term effectiveness of a non-formal co-curricular educational programme based on a campus ecogarden at a Hong Kong university in developing pro-sustainability awareness, attitudes and behaviour among undergraduate students. This service-based, nature-based experiential learning programme, termed the Ecogarden Farmer and Biodiversity Surveyor, has been running at the university since 2015. The programme is divided into two consecutive phases: a training phase comprising various learning activities and a successive internship phase consisting of the all-round practical tasks involved in managing the garden. A retrospective evaluation of the programme using phenomenographic approach and content analysis was adopted to reveal the diversity of students’ learning experience, as the indicators of the success of the programme. Of 112 participants from 4 cohorts, 32 completed online questionnaires, and semi-structured interviews were successfully conducted with twelve participants, three from each of the four cohorts. The results indicated that the programme’s outcomes could be categorised into five themes. Most outcomes fit into the theme ‘an increase in knowledge and skill level’, followed by ‘rise in environmental awareness’, ‘facilitation of personal growth’ and ‘enhancement of career development’. Many structural experiences revealed may suggest the success of the programme. The longer the participants had participated in the programme, the more in-depth and diversified reflections relating to personal development were mentioned. This study provides critical insights into the validity of retrospective programme evaluation for assessing the long-term impact of EfS programmes by introducing a cross-sectional study of different cohorts as a serial time-point sampling strategy.